Interests and Contradictions between Turkey and Russia in the South Caucasus in New Geopolitical Realities (2010-2016) - Sakoyan, Taron (History and Culture, 2021)
The purpose of the article is to analyze the interests and contradictions between Russia and Turkey in the South Caucasus, which have been aggravated in many aspects by the influence of the Syrian and Ukrainian crises. In these circumstances, Azerbaijan became a key player for Ankara, which allowed the latter to gradually move on its interests in the region. Meanwhile, the formation of the EAEU with the participation of Armenia (without any preconditions on its end) negatively affected the latter’s factor, first of all, for Moscow as an ally. On top of it, Turkey and Azerbaijan, contrary to the interests of Armenia, significantly strengthened their geopolitical factors before Russia, against the backdrop of West’s political and economic sanctions against Moscow.
Keywords: Russia; Turkey; the South Caucasus; balance of power; Syrian crisis; Ukrainian crisis; EAEU; factor; Armenia; Karabakh conflict